Electrically guided versus imaging-guided implant of the left ventricular lead in cardiac resynchronization therapy: a study protocol for a double-blinded randomized controlled clinical trial (ElectroCRT) - Stephansen, Charlotte (Trials, 2018)
BACKGROUND: Cardiac resynchronization therapy (CRT) is an established treatment in patients with heart failure and prolonged QRS duration where a biventricular pacemaker is implanted to achieve faster activation and more synchronous contraction of the left ventricle (LV). Despite the convincing effect of CRT, 30–40% of patients do not respond. Among the most important correctable causes of non-response to CRT is non-optimal LV lead position. METHODS: We will enroll 122 patients in this patient-blinded and assessor-blinded, randomized, clinical trial aiming to investigate if implanting the LV lead guided by electrical mapping towards the latest LV activation as compared with imaging-guided implantation, causes an excess increase in left ventricular (LV) ejection fraction (LVEF). The patients are randomly assigned to either the intervention group: preceded by cardiac computed tomography of the cardiac venous anatomy, the LV lead is placed according to the latest LV activation in the coronary sinus (CS) branches identified by systematic electrical mapping of the CS at implantation and post-implant optimization of the interventricular pacing delay; or patients are assigned to the control group: placement of the LV lead guided by cardiac imaging. The LV lead is targeted towards the latest mechanical LV activation as identified by echocardiography and outside myocardial scar as identified by myocardial perfusion (MP) imaging. The primary endpoint is change in LVEF at 6-month follow up (6MFU) as compared with baseline measured by two-dimensional echocardiography. Secondary endpoints include relative percentage reduction in LV end-systolic volume, all-cause mortality, hospitalization for heart failure, and a clinical combined endpoint of response to CRT at 6MFU defined as the patient being alive, not hospitalized for heart failure, and experiencing improvement in NYHA functional class or/and > 10% increase in 6-minute walk test. DISCUSSION: We assume an absolute increase in LVEF of 12% in the intervention group versus 8% in the control group. If an excess increase in LVEF can be achieved by LV lead implantation guided by electrical mapping, this study supports the conduct of larger trials investigating the impact of this strategy for LV-lead implantation on clinical outcomes in patients treated with CRT. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02346097. Registered on 12 January 2015. Patients were enrolled between 16 February 2015 and 13 December 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2930-y) contains supplementary material, which is available to authorized users.